Liability Without Fault in Environmental Dispute Settlement: The Per-spec-tive of Law No. 32 of 2009 Concerning Environmental Protection and Man-agement - Azhar, Muhammad Yasir; Lubis, Saddan Dintara (IHSA Institute, 2025)
Environmental issues in Indonesia are becoming increasingly complex, driven by the rapid growth of industry and the exploitation of natural resources that disregard the principles of sustainability. This study aims to analyze the implementation of the principle of liability without fault in resolving environmental disputes, as stipulated in Law Number 32 of 2009 concerning Environmental Protection and Management. This principle provides a platform for injured parties to seek legal accountability without having to prove fault, in line with the polluter pays principle. The approach used in this study is a normative juridical method, relying on secondary data in the form of laws and regulations, legal literature, and previous research findings. The findings indicate that the existence of the principle of strict liability in Article 88 strengthens the legal basis for filing civil lawsuits for redress of environmental damage, even in conditions without elements of intent or negligence. Dispute resolution can be pursued through litigation or non-litigation channels such as mediation and arbitration. These findings are significant in promoting ecological justice, expanding public access to environmental justice, and strengthening legal responsibility for business actors. This study concludes that it is necessary to strengthen socialization efforts and enforce the law firmly and consistently so that the principle of liability without fault can function optimally as a preventive and corrective legal instrument